2003
DOI: 10.1016/j.humimm.2003.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Pemphigus vulgaris in Jewish patients is associated also with HLA-A region genes

Abstract: It has been estimated that only 10% of persons infected with Mycobacterium tuberculosis will ever develop clinical disease. As for the host genetic factors, there have been some studies on HLA association with tuberculosis susceptibility, however its association with disease severity or drug resistance has been rarely reported. To investigate the association of HLA polymorphism and disease susceptibility to pulmonary tuberculosis, HLA-DRB1 and DQB1 genes were analyzed in 160 Korean patients with pulmonary tube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Tables 3 and 4 summarize the results of the HLA typing of the Spanish patients and controls. HLA typing of the Jewish PV and control panels has been previously published (20).…”
Section: Resultsmentioning
confidence: 99%
“…Tables 3 and 4 summarize the results of the HLA typing of the Spanish patients and controls. HLA typing of the Jewish PV and control panels has been previously published (20).…”
Section: Resultsmentioning
confidence: 99%
“…The control group was selected for the HLA alleles known to be associated with PV although the patients were randomly selected from our outpatient clinic. All patients and controls had been typed by DNA based techniques for their HLA class I and class II genes [19]. The diagnosis of PV was based on clinical, immunologic, and imunohistopathologic criteria [1].…”
Section: Materials and Methods Patients And Controlsmentioning
confidence: 99%
“…These markers span the entire major histocompatibility complex (MHC) [16 -18]. We have found that specific alleles of markers, which were mapped to the class I region close to HLA-A, were highly associated with the pemphigus haplotypes [19]. These findings warranted a more extensive mapping attempt using the single nucleotide polymorphism (SNP) approach [20].…”
Section: Introductionmentioning
confidence: 99%
“…There seems to be a fairly strong genetic linkage of PV with HLA class II antigens, while the prevalence and incidence of this disease is higher in the Jewish race and in countries around the Mediterranean Sea. 2,[5][6][7][8][9][10][11] Oral lesions are common in PV and patients suffering from PV usually present with irregularly shaped oral erosions, which are painful and slow to heal. 1,2,[12][13][14] Diagnosis is based on three main criteria: Clinical findings, histopathological findings of lesion biopsy, and direct immunofluorescence (DIF) on normalappearing perilesional skin and /or oral mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…Pemphigus vulgaris is a rare disease in northern Europe and the USA. There seems to be a fairly strong genetic linkage of PV with HLA class II antigens, while the prevalence and incidence of this disease is higher in the Jewish race and in countries around the Mediterranean Sea 2,5–11 …”
Section: Introductionmentioning
confidence: 99%